Multiple genotypes of enterovirus G carrying a papain-like cysteine protease (PL-CP) sequence circulating on two pig farms in Japan: first identification of enterovirus G10 carrying a PL-CP sequence - Sekiguchi, Yuya; Nagata, Ayaka; Sunaga, Fujiko; Oi, Toru; Imai, Ryo; Madarame, Hiroo; Katayama, Yukie; Oba, Mami; Okabayashi, Tamaki; Misawa, Naoaki; Oka, Tomoichiro; Mizutani, Tetsuya; et al. (Archives of virology, 2020)
Two and three genotypes of enterovirus G (EV-G) carrying a papain-like cysteine protease (PL-CP) sequence were detected on two pig farms and classified into genotypes G1 and G10, and G1, G8, and G17, respectively, based on VP1 sequences. A G10 EV-G virus bearing a PL-CP sequence was detected for the first time. Phylogenetic analysis of the P2 and P3 regions grouped the viruses by farm with high sequence similarity. Furthermore, clear recombination break points were detected in the 2A region, suggesting that PL-CP EV-G-containing strains gained sequence diversity through recombination events among the multiple circulating EV-G genotypes on the farms.